Merely A Smell - Samra, Maher Abi (Les Films D'Ici, 2007)
Verzio FF Submission Summer 2006: the Israeli war on Lebanon. A boat embarks for besieged Beirut to evacuate foreign nationals. From under the rubble of destroyed buildings, relief workers pull the bodies of the dead. Moving between light and darkness, life and its extinction, bodies redraw the boundaries of other bodies, the smell of death cloaking all.